Self-Efficacy and Intensity of the Use of Social Media on Consumption Behavior: Case Study in the Economics Faculty of Yogyakarta State University - Nyimas Yuhanis Sartika; Sugiharsono Sugiharsono (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: This study aims to examine the effect of self-efficacy and the intensity of social media use on student consumption behaviour, both partially and simultaneously. It belongs to causal associative research with a quantitative approach. The population of this study was 476 undergraduate students batch of 2016 in the Faculty of Economics, Yogyakarta State University (YSU). A sample of 217 students was selected through a proportional cluster random sampling technique. Data were collected using questionnaires that were previously tested for validity and reliability. The data analysis technique used a multiple regression. Keywords: consumption behavior, self-efficay, intensity of the use of social media Efikasi Diri dan Intensitas Penggunaan Media Sosial Terhadap Perilaku Konsumsi: Stadi Kasus di Fakultas Ekonomi Universitas Negeri Yogyakarta Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh efikasi diri dan intensitas penggunaan media sosial terhadap perilaku konsumsi mahasiswa, baik secara parsial maupun simultan. Penelitian ini termasuk penelitian asosiatif kausal dengan pendekatan kuantitatif. Populasi penelitian ini adalah 476 mahasiswa Strata-1 Fakultas Ekonomi Universitas Negeri Yogyakarta angkatan 2016. Adapun jumlah sampel 217 mahasiswa yang diambil dengan teknik proportional cluster random sampling. Data dikumpulkan dengan kuisioner yang telah diuji validitas dan reliabilitasnya. Teknik analisis data yang digunakan adalah regresi berganda. Kata kunci: perilaku konsumsi, efikasi diri, intensitas penggunaan media sosial